Biodiversity of urban street trees in Italian cities: a comparative analysis. (7th July 2022) - Bartoli, F.; Savo, V.; Caneva, G.
Abstract: Street trees are key elements in urban ecosystems from several points of view, and different species can have different functions (i.e., ecological, socio-economic). As such, a careful biodiversity assessment is pivotal. We evaluated urban street trees in 15 Italian cities along a geographical and bioclimatic gradient. The data was obtained from scientific literature and Garden Service Offices of the cities. The distribution patterns of the species were analyzed in terms of taxonomy, chorology, and tree size. We registered 277 tree species belonging to 48 families. The species richness is very variable in analyzed cities, and it is not directly correlated with the city's size. Only three species ( Platanus × hispanica, Celtis australis and Quercus ilex ) are common to almost all cities, while 41.52% of the species are present only in one city. The comparative analysis of species, considering the floristic and city distribution, showed different results, highlighting Pinaceae as the most common family. The chorological analysis shows a predominance of exotic species and a good relationship with the bioclimatic conditions of cities. A selection of the species, as street trees to maximize their ecological and socio-economic functions, is pivotal in urban landscaping and green management.